KOMUNIKASI ORGANISASI PEMERINTAH DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK PADA DISTRIK SENTANI JAYAPURA - Fetni; Taslim Fait; La Ode Aslim (Journal Publicuho, 2024)
This research aims to determine Government Organizational Communication in Improving the Quality of Public Services at the Sentani Jayapura District Office. The research uses a qualitative descriptive method to detail organizational communication and its impact on the Sentani District Office, which provides public services in Jayapura City. Considering the analysis, It was discovered that the organizational communication climate is very important and can improve how well public services are provided at the Sentani District Office in Jayapura City. Creating a good communication climate, in this case, involves instilling honesty, trust, and openness in communication, listening to downward communication, and participating in decision-making. These are important factors that indicate two-way communication at the Sentani District Office in Jayapura City. Involving members of the organization in the decision-making process further illustrates that a comfortable and conducive working environment can be created at the Sentani District Office in Jayapura City.